2021
DOI: 10.1017/s1479262121000381
|View full text |Cite
|
Sign up to set email alerts
|

Stress tolerance indices for the identification of low phosphorus tolerant introgression lines derived from Oryza rufipogon Griff.

Abstract: Soil phosphorus (P) deficiency is one of the major challenges for the cultivation of rice worldwide because it limits the growth and productivity of the crop. Therefore, the ability to grow in P-deficit soils is an important trait for rice cultivation. O . rufipogon Griff., a wild relative of rice, is a source of genetic variation for low phosphorus tolerance. The present study was undertaken to identify low P stress-tolerant introgression lines by analysing stress tolerance indices of 40 introgression lines o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…Stress tolerance indices have also been used as a selection criterion in several low‐P tolerance studies (Basavaraj et al, 2021; Manoj et al, 2023). In the current study, the associations observed among the five stress tolerance indices and grain yield corroborate with the previous studies (Manoj et al, 2023; Singh et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Stress tolerance indices have also been used as a selection criterion in several low‐P tolerance studies (Basavaraj et al, 2021; Manoj et al, 2023). In the current study, the associations observed among the five stress tolerance indices and grain yield corroborate with the previous studies (Manoj et al, 2023; Singh et al, 2018).…”
Section: Discussionmentioning
confidence: 99%